Neural-network model of physical loads versus functional activity of blood neutrophils in skilled athletes in off-season - Bazarin, K. P.; Savchenko, A. A. (Theory and Practice of Physical Culture, 2018)
High physical loads in modern sports are known to increase the exposure to immune system disorders. Subject to the study were neutrophil granulocytes for the reason that the microbe immunity largely depends on the phagocytic activity. ?hemiluminescent activity of neutrophil granulocytes may result in a `respiratory explosion` that occurs due to interaction of cells with objects of phagocytosis. ?hemiluminescent process parameters are highly informative as indicators of functional activity of neutrophil granulocytes.